2011
DOI: 10.1039/c1cp22168j
|View full text |Cite
|
Sign up to set email alerts
|

Simulating water with rigid non-polarizable models: a general perspective

Abstract: Over the last forty years many computer simulations of water have been performed using rigid non-polarizable models. Since these models describe water interactions in an approximate way it is evident that they cannot reproduce all of the properties of water. By now many properties for these kinds of models have been determined and it seems useful to compile some of these results and provide a critical view of the successes and failures. In this paper a test is proposed in which 17 properties of water, from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
995
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 838 publications
(1,043 citation statements)
references
References 347 publications
43
995
3
2
Order By: Relevance
“…This software has been validated over a broad range of applications (Macpherson and Reese 2008;Ritos et al 2013;Dongari et al 2011) including flow of water through carbon nanotubes Ritos et al 2014;. In all our simulations we use the TIP4P/2005 water model (Abascal and Vega 2005;Vega and Abascal 2011) with a Lennard-Jones potential for water-carbon interactions that has the following intermolecular parameters: σ CO = 0.319 nm and ǫ CO = 0.427 kJ mol −1 .…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…This software has been validated over a broad range of applications (Macpherson and Reese 2008;Ritos et al 2013;Dongari et al 2011) including flow of water through carbon nanotubes Ritos et al 2014;. In all our simulations we use the TIP4P/2005 water model (Abascal and Vega 2005;Vega and Abascal 2011) with a Lennard-Jones potential for water-carbon interactions that has the following intermolecular parameters: σ CO = 0.319 nm and ǫ CO = 0.427 kJ mol −1 .…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…These models vary in the number of considered interaction sites, their flexibility or rigidity and their treatment or neglect of polarizability. Reviews of water models [1][2][3] have addressed their relative merits to model the thermodynamic (e.g. phase diagram or heat capacities), structural and dynamic properties of water.…”
Section: Introductionmentioning
confidence: 99%
“…62 The T MD for mW UQ is 23 K below the T m , similar to the mW model and 5% lower than the experimental value of 277 K. The lack of hydrogen atoms in this family of coarse-grained models results in the loss of all rotational contributions to the entropy. This precludes the possibility of simultaneously reproducing T m and ΔH m .…”
Section: Sensitivity Of the Properties Of The Watermentioning
confidence: 59%
“…64 Vega and Abascal provided a comprehensive summary of properties of rigid nonpolarizable atomistic models of water and demonstrated that trade off in the accuracy in certain properties results in dramatic changes in the global representability of the models. 62 Due to the effect of averaging over degrees of freedom, coarse-grained models are not capable of reproducing all properties of interest of the finer resolution model (or the experimental system) simultaneously. Therefore, when a coarse-grained model is parametrized, some properties must be prioritized and it must be ensured that the model derived has adequate fidelity for those properties.…”
Section: Sensitivity Of the Properties Of The Watermentioning
confidence: 99%